55th RVR COB recognition rites - Ramon V. del Rosario College of Business - De La Salle Universty, Manila (Animo Repository, 2021)
The Ramon V. del Rosario College of Business held its 55th RVR COB Recognition Rites virtually via Zoom on September 11, 2021 (Saturday) at 10:00 AM. The invited participants and guests were given access to the Zoom link at least 30 minutes before the event starts. Data privacy guidelines such as no recording of the video, archiving of the video in DLSU Library, etc. was implemented. Important reminders were played at the start of the event.